Organizational Behavior Explained: Definition, meaning, Nature, Model - Alka (Innovative Research Thoughts, 2017)
Organizational Behavior (OB) is the study of human behavior in organizational settings, the interface between human behavior and the organization, and the organization itself. Organizational Behavior researchers study the behavior of individuals primarily in their organizational roles. One of the main goals of organizational behavior is to revitalize organizational theory and develop a better conceptualization of organizational life. As a multi-disciplinary field, organizational behavior has been influenced by developments in a number of allied disciplines including sociology, psychology, economics, and engineering as well as by the experience of practitioners.